Non-enzymatic antioxidant blood plasma profile in the period of high training loads of elite speed skaters in the altitude - Proskurnina, E.; Martynov, D.; Yakushkin, A.; Zelenkova, I. (Sports Medicine and Health Science, 2023)
At the altitude, hypoxia and training load are key factors in the development of oxidative stress. Altitude-induced oxidative stress is developed due to the depletion of antioxidant potential. In the current study, we examined the non-enzymatic antioxidant profile of blood plasma in 7 males and 5 females specializing in speed skating at a 21-day training camp at 1 850 ?m above sea level. Training included: cycling, roller skating, ice skating, strength training, and special training. At the start point and the endpoint, total hemoglobin mass (tHb-mass), hemoglobin concentration, and circulating blood volume were determined. Antioxidant profiles, hypoxic doses, hypoxic impulses, and training impulses were assessed at 3, 6, 10, 14, and 18 days. Antioxidant profiles consisting of "urate" and "thiol" parts were registered with chemiluminometry. In the training dynamics, antioxidant parameters changed individually, but in total there was a decrease in the "urate" capacity by a factor of 1.6 (p ?= ?0.001) and an increase in the "thiol" capacity by a factor of 1.8 (p ?= ?0.013). The changes in "urate" capacity positively correlated (rS ?= ?0.40) and the changes in "thiol" capacity negatively correlated (rS ?= ?-0.45) with changes in tHb-mass. Both exercise and hypoxic factors affect the antioxidant parameters bidirectionally. They correlated with a decrease in thiol capacity and with an increase in urate capacity. The assessment of the non-enzymatic antioxidant profile can be a simple and useful addition to screening the reactive oxygen species homeostasis and can help choose the personalized training schedule, individualize recovery and ergogenic support.